2020
DOI: 10.21107/jps.v7i2.8722
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL SCREENING OF ETHANOLIC EXTRACT: a Preliminary Test on Five Medicinal Plants on Bangkalan

Abstract: This study is preliminary research of secondary metabolite potential from medicinal Herb Madura. This study aims to know the medicinal plants used in the medicinal herb Madura and the phytochemical content contained in these medicinal plants.  The method used in this study is a survey to know the kinds of medicinal plants used in Madura Herb. Then a phytochemical screening test for the medicinal plant was performed. The phytochemical screening test used are alkaloids, steroids, saponins, and flavonoids.  Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
3
9
1
Order By: Relevance
“…The results obtained can be seen in Table 2. However, this study's results differ from those of Muharrami et al (2020), which succeeded in identifying the presence of saponin compounds contained in the stems of Parameria laevigata, a rhizome of Kaempferia galanga L. (kencur), a rhizome of C. zanthorrhiza and extracts of Punica granatum (pomegranate). The standard saponin test indicates a positive result for the presence of saponins if a relatively stable foam is observed when the sample is dissolved in hot water (Ashour et al 2019).…”
Section: Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…The results obtained can be seen in Table 2. However, this study's results differ from those of Muharrami et al (2020), which succeeded in identifying the presence of saponin compounds contained in the stems of Parameria laevigata, a rhizome of Kaempferia galanga L. (kencur), a rhizome of C. zanthorrhiza and extracts of Punica granatum (pomegranate). The standard saponin test indicates a positive result for the presence of saponins if a relatively stable foam is observed when the sample is dissolved in hot water (Ashour et al 2019).…”
Section: Resultscontrasting
confidence: 92%
“…The results of the Mayer test showed various reaction responses, which indicated qualitatively a range in the alkaloid content of the accessions studied. These results conform with the research reported by Muharrami et al (2020), which stated that for the alkaloid tests using Dragendorf and Wagner reagents, a yellow to brown precipitate was obtained, indicating a positive result for the content of alkaloid phytochemical compounds in the C. zanthorrhiza rhizome. Alkaloid compounds have bioactivity properties such as antitumor and anticancer, antispasmodic and antibacterial effects.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The rats were fed 4 h after receiving the drug and had unlimited access to water throughout the study. Under light anesthesia by diethyl ether, blood samples (0.5 ml) were collected by a heparinized tube from the retro-orbital venous plexus [33] at time intervals of 0, 0.25, 0.5, 1, 2, 4, 8, 24, and 48 h after dosing. The blood samples were centrifuged instantly at 4000 rpm for 5 min (PLC-012, Gemmy Industrial Corp, Taiwan).…”
Section: In Vivo Pharmacokinetic Study Of the Bi-laminated Odf Contai...mentioning
confidence: 99%